Penyuluhan Hukum Pencegahan Penggunaan Narkotika di Desa Sungai Pinang Kabupaten Kampar - Yudi Krismen; Zulkarnain S; Riadi Asra Rahmad; Raden Imam Al-Hafis; Elsi Elvina; Nando Tri Nugroho (I-Com: Indonesian Community Journal, 2025)
Narcotics are not a new problem in Indonesia. The number of cases of drug abuse in Indonesia is increasingly worrying. Drug users are currently not only among adults but also among children. As a result of the rampant news and the high number of drug cases, the Sungai Pinang Village Community in Kampar Regency are worried that drug use will appear in Sungai Pinang Village. Based on these problems, the community service team provided legal counseling on preventing drug use in Law Number 35 of 2009 concerning Narcotics. The legal counseling method used was a lecture method accompanied by PPT. The results of the community service in the form of legal counseling, the community service team succeeded in providing knowledge to the Sungai Pinang Village Community in Kampar Regency about narcotics and the legal regulations that govern them. This counseling is very useful for educating the community about narcotics and the legal regulations that govern them so that drug abuse does not occur in Sungai Pinang Village, Kampar Regency.